(untitled) (Annals of Medical Research, 2021)
Aim: This study was made to determine the frequency of the death anxiety, depression, and anxiety of the patients over the age of 50 years at the tertiary care cancer center in Turkey.Material and Methods: Patients were divided into three groups as the ones with tumoral disease (group 1), the ones with fracture (group 2), and the ones who have not tumor or fracture. All the participants were evaluated with geriatric anxiety scale (GAS), geriatric depression scale (GDS), and death anxiety scale (DAS).Results: There are 16(%17) patients in group 1, 27(%29) patients in group 2 and 50(%53) patients in group 3. Moreover, It was found that GAS, GDS, and DAS points were found to be similar and there was no significant difference between groups according to depression levels (p>0.05).It was found that age (OR=1.09; %95GA=1.01-1.19), tumor presence (OR=8.7; %95GA=1.02-74.43), GDS point (OR=1.21; %95GA=1.01-1.45) and being single/divorced (OR=0.05; %95GA=0.01-0.08) had significant effect on death anxiety. Conclusion: Geriatric anxiety, death anxiety, and depression of patients over age of 50 years in our hospital’s orthopedics clinic are similar independent of the presence of tumor, other diseases, tumor or fracture. And death anxiety is increasing with age in all the groups. Besides, old age, tumor presence, high level of GDS and being unmarried are the factors increasing the death anxiety.